Generalized (G'/G)-expansion method for some soliton wave solutions of Burgers-like and potential KdV equations - İnç, Mustafa; Ic, Unal; Inan, Ibrahim Enam; Gomez-Aguilar, Jose Francisco (Wiley, 2022)
In this paper, we implement a generalized (G'/G)-expansion method for some soliton wave solution Burgers-like equation and potential KdV equation. These solutions are hyperbolic function solutions, trigonometric function solutions, exponential function solutions and rational function solutions. In addition, graphs of some solutions and numerical explanations of these graphs are given. Also, we have compared our solutions for the equations with some other solutions previously found by using various methods.
Keywords: Burgers-like equation; generalized (G'/G)-expansion method; potential KdV equation